Understanding health insurance : a guide to billing and reimbursement - Green, Michelle A.; Rowell, Jo Ann C., 1934- (Clifton Park, NY : Delmar Cengage Learning, 2015)
'Understanding Health Insurance, Eleventh Edition, is the essential learning tool your students need when preparing for a career in medical insurance billing. This comprehensive and easy-to-understand text is fully-updated with the latest code sets and guidelines, and covers important topics in the field like managed care, legal and regulatory issues, coding systems, reimbursement methods, medical necessity, and common health insurance plans. The eleventh edition has been updated to include new legislation that affects healthcare, ICD-10-CM coding, implementing the electronic health record, the Medical Integrity Program (MIP), medical review process, and more. The practice exercises in each chapter provide plenty of review, and the accompanying workbook provides even more application-based assignments and additional case studies for reinforcement. Includes free online StudyWARE software that allows students to test their knowledge, free online SimClaim CMS-1500 claims completion software, and free-trial access to Ingenix's EncoderPro.com--Expert encoder software.'--Publisher's website.
Health Insurance Specialist Career -- Introduction to Health Insurance -- Managed Health Care -- Processing an Insurance Claim -- Legal and Regulatory Issues -- ICD-9-CM Coding -- ICD-10-CM Coding -- CPT Coding -- HCPCS Level II Coding -- CMS Reimbursement Methodologies -- Coding for Medical Necessity -- Essential CMS-1500 Claim Instructions -- Commercial Insurance -- Blue Cross Blue Shield -- Medicare -- Medicaid -- TRICARE -- Workers' Compensation.
This book includes online access at http://www.cengagebrain.com, please refer library stff for the password
Includes bibliographical references (p. 711-713) and index.
Keywords: Insurance, Health -- United States -- Forms; Insurance, Health -- United States -- Problems and Exercises; Insurance Claim Reporting -- United States -- Forms; Insurance Claim Reporting -- United States -- Problems and Exercises; Insurance Claim Review -- United States -- Forms; Insurance Claim Review -- United States -- Problems and Exercises; Health insurance; Health insurance claims; United States